Development of Long QT Syndrome Detection Using SciPy - Himawan, Moses; Sadrawi, Muammar (Indonesia International Institute for Life Sciences, 2023)
Long QT syndrome (LQTS) is a type of arrhythmia that manifests itself as the elongation of the QT interval. LQTS is caused due to different disorders in the sodium and potassium channels which results in reduced activity of the cardiac muscle. To diagnose LQTS, an algorithm is used to detect the elongated QT interval through detection of the peaks using Python. The current build of the algorithm is able to detect different ECG graphs for their QT interval with relative accuracy however is not capable of detecting the different components if the graph has too much noise or if they have irregular wavelengths due to other cardiovascular disease (CVD).